Study of composite array for multi-resolution digital beamforming - Cui, Wei (2015)
Digital beamforming, the bridge between antenna technology and digital technology, has been highly recognized in the applications of radar communications, wireless communications, and radio astronomy. Particularly, the adaptive beamformer in digital beamforming is critical in high performance radar systems.